COMMON MARKET ORGANIZATION A NEW CHALLENGE IN REFORMING THE COMMON AGRICULTURAL POLICY - Jean, Andrei; Dusmanescu, Dorel; Voicilas, Marius (Economics of Agriculture, 2011)
The achievement of any policy, including CAP, involves building a complex operation mechanism, tools and specifc levers to ensure the achievement of the objectives at the highest degree. The substantiation of these instruments and their adjustment to the new conditions imposed by CAP feld application requires both political measures imposed by the EU Member States as well coordination with the functional mechanism of the free market, in the general context in combating distortions in their application.